The role of local wisdom in creating peace and social harmony in villages: cultural and traditional perspectives - Tohari, Amin (Jurnal Konseling dan Pendidikan, 2025)
This study explores the role of local wisdom in fostering peace and social harmony within village communities, emphasizing cultural and traditional perspectives. Local wisdom, embedded in various aspects of community life such as rituals, customs, and norms, serves as a powerful tool in conflict resolution and social cohesion. By utilizing a qualitative approach through literature review, this paper examines how indigenous knowledge and values promote peaceful interactions, respect, and collective responsibility. The findings reveal that local wisdom, manifested in practices like adat (traditional law), communal decision-making processes, and cultural ceremonies, plays a vital role in maintaining balance and preventing disputes in rural areas. Furthermore, local wisdom fosters a strong sense of identity and belonging, encouraging collaboration and mutual understanding among community members. These cultural traditions and practices provide a sustainable framework for managing differences and promoting unity in diversity. The study highlights the importance of preserving and revitalizing local wisdom as an essential element in achieving long-term peace and social harmony, particularly in the face of modernization and external influences. By safeguarding these traditions, village communities can continue to thrive in an environment of respect, trust, and solidarity.